2015
DOI: 10.1159/000381459
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thyroid Hormones on Estrogen Receptor α-Dependent Transcriptional Mechanisms in Ventromedial Hypothalamus and Preoptic Area

Abstract: Elevated levels of thyroid hormones (TH) reduce estradiol (E2)-dependent female sexual behavior. E2 stimulates progesterone receptor (Pgr) and oxytocin receptor (Oxtr) within the ventromedial hypothalamus and preoptic area, critical hypothalamic nuclei for sexual and maternal behavior, respectively. Here, we investigated the impact of TH on E2-dependent transcriptional mechanisms in female mice. First, we observed that triiodothyronine (T3) inhibited the E2 induction of Pgr and Oxtr. We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
(80 reference statements)
2
3
0
Order By: Relevance
“…A dose-dependent decrease in DII expression was observed in abdominal arteries from HCB-treated rats, which, together with the lower levels of T4 in serum, could be responsible for the decrease in arterial T3 levels. Moreover, it has been widely established that a decrease in T3 causes a reduction in ER expression (Davis et al, 2002;Faustino et al, 2015) which could be in line with the decrease in ER expression observed in this work.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…A dose-dependent decrease in DII expression was observed in abdominal arteries from HCB-treated rats, which, together with the lower levels of T4 in serum, could be responsible for the decrease in arterial T3 levels. Moreover, it has been widely established that a decrease in T3 causes a reduction in ER expression (Davis et al, 2002;Faustino et al, 2015) which could be in line with the decrease in ER expression observed in this work.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Likewise, the histological changes of hypothyroidism ovaries and testes are in agreement with previous reports (Dijkstra et al 1996, Silva et al 2011. The ventromedial hypothalamus neurons are critical hypothalamic nuclei for the integration of energy balance within the reproductive system (Faustino et al 2015, Carmo-Silva & Cavadas 2017, Sá & Fonseca 2017. Pituitary chromophobes represent degranulated chromophils, inactive reserve cells, or the primary stage of the formation of chromophils (Yoshimura et al 1969).…”
Section: Discussionsupporting
confidence: 89%
“…Key factors regulating social behaviors are oxytocin (OXT) and arginine vasopressin (AVP) and they have been studied extensively using different animal models Bielsky et al 2005;Choleris et al 2003;Crawley et al 2007;Ferguson et al 2000;Yu et al 2016) (Champagne et al 2001;Pedersen 1997;Pedersen et al 2006) (Bosch & Neumann 2012;Calcagnoli et al 2014a;Calcagnoli et al 2014b;Ferris & Potegal 1988;Pagani et al 2015). In addition, several studies have shown that thyroid hormones are also implicated in the regulation of those neuropeptides and their signaling Adan et al 1993;Burbach et al 1993;Campo Verde Arbocco et al 2015;Ciosek & Drobnik 2004;Dellovade et al 1999;Faustino et al 2015;Vasudevan et al 2001a;Vasudevan et al 2001b). Thus, it is possible that alterations in the determinants of brain thyroid hormone action contribute to social behaviors.…”
mentioning
confidence: 99%